Michael Polanyi and His Generation : Origins of the Social Construction of Science. - Nye, Mary Jo (University of Chicago Press, 2011)
In Michael Polanyi and His Generation, Mary Jo Nye investigates the role that Michael Polanyi and several of his contemporaries played in the emergence of the social turn in the philosophy of science. This turn involved seeing science as a socially based enterprise that does not rely on empiricism and reason alone but on social communities, behavioral norms, and personal commitments. Nye argues that the roots of the social turn are to be found in the scientific culture and political events of Europe in the 1930s, when scientific intellectuals struggled to defend the universal status of scientific knowledge and to justify public support for science in an era of economic catastrophe, Stalinism and Fascism, and increased demands for applications of science to industry and social welfare. At the center of this struggle was Polanyi, who Nye contends was one of the first advocates of this new conception of science. Nye reconstructs Polanyi's scientific and political milieus in Budapest, Berlin, and Manchester from the 1910s to the 1950s and explains how he and other natural scientists and social scientists of his generation--including J.D. Bernal, Ludwik Fleck, Karl Mannheim, and Robert K. Merton--and the next, such as Thomas Kuhn, forged a politically charged philosophy of science, one that newly emphasized the social construction of science.